2021
DOI: 10.1111/trf.16339
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood type association with SARS‐CoV‐2 infection mortality: A single‐center population in New York City

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has a variable clinical course with significant mortality. Early reports suggested higher rates of SARS‐CoV‐2 infection in patients with type A blood and enrichment of type A individuals among COVID‐19 mortalities. Study Design and Methods The study includes all patients hospitalized or with an emergency department (ED) visit who were tested for SARS‐CoV‐2 between March 10, 2020 and June 8, 2020 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
(75 reference statements)
0
19
0
Order By: Relevance
“…Already in the early studies of the SARS‐CoV‐2 pandemic, the association of ABO blood group type with the SARS‐CoV‐2 infection has been noticed, where the blood group A was associated with an increased risk of disease compared to the blood group O that was associated with a decreased risk for severe COVID‐19 illness 1,2 . Although certain studies failed to confirm such association, 3,4 several large cohort studies, 5,6 reviews, and meta‐analyses 7–10 confirmed that the individuals with blood group A are more susceptible and those with blood group O are less vulnerable for COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…Already in the early studies of the SARS‐CoV‐2 pandemic, the association of ABO blood group type with the SARS‐CoV‐2 infection has been noticed, where the blood group A was associated with an increased risk of disease compared to the blood group O that was associated with a decreased risk for severe COVID‐19 illness 1,2 . Although certain studies failed to confirm such association, 3,4 several large cohort studies, 5,6 reviews, and meta‐analyses 7–10 confirmed that the individuals with blood group A are more susceptible and those with blood group O are less vulnerable for COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of ABO blood group in COVID-19 has previously been described 9,18 . A significant overrepresentation of AB group and the non-significant but trending underrepresentation of the O group within our cohort appear to be in accordance with other groups’ suggestion that O individuals could be less susceptible to SARS-CoV-2 infection 7,8 , given that every individual in our study was proved to be infected.…”
Section: Discussionmentioning
confidence: 91%
“…The involvement of ABO blood group in COVID-19 has previously been described[3, 12]. The exact mechanism of action remains elusive, but could be associated to circulating natural anti-A and anti-B antibodies, or a low efficiency furin cleavage in O group individuals[9].…”
Section: Discussionmentioning
confidence: 99%
“…[ 105 ]. In Brazil, the variants IL17A and IL17F are associated with the development of cardiomyopathy [ 106 ] In the African/African-American population, p.Arg514-Gly, a polymorphism of ACE2, is associated with cardiovascular and pulmonary conditions [ 107 ] In Genome-wide Association Study (GWAS) in Italian and Spanish hospitals, a 3p21.31 gene cluster encompassed the SLC6A20, LZTFL1, CCR9, FYCO1, CXCR6, and XCR1 genes [ 108 ] Genetic polymorphisms of Interferon-γ Production In the Brazilian population, genotypes and alleles of IL12B and IL-10 could be associated with a failure to regulate Th1 responses, IFNγ production, and an increased risk of chronic CD cardiomyopathy [ 109 ] Interferon-gamma gene (IFNG) + 874 T/A polymorphism could be related to a predisposition to CD in the South American population [ 110 ] The single nucleotide polymorphism (SNP) rs6598045 of the interferon-induced transmembrane protein 3 (IFITM3) gene correlates with COVID-19 fatality rates [ 111 ] Populations with a low allele frequency of rs1990760 (T allele) in IFIH1 (InterFeron-Induced Helicase 1; MDA5) are associated with less IFN-beta expression and potential susceptibility to COVID-19 infection [ 112 ] ABO blood group system Inconclusive studies found an increase in blood group B patients dying suddenly from CD [ 113 ] The histo-blood group system explored by GTA, GTB, FUT II, and FUT III glycosyltransferases found that B plus AB secretor phenotypes are related to megaesophagus and megacolon in CD [ 114 ] GWAS found blood group A is associated with COVID-19 and respiratory failure [ 111 ] Type A blood is associated with the risk of in-hospital death [ 115 ] Ethnicity CD with megacolon, calibre and length of the rectosigmoid depends on altitude, ethnicity, and diet [ 116 ] COVID-19 presents an increased risk depending on the population studied, e.g. Black and Asian compared to white subjects had increased risk infection of COVID-19 [ 117 ] In Mexico, native peoples have a higher risk of death due to COVID-19 [ 118 ] Dysregulated immunothrombosis Hypercoagulability The activation of haemostasis is related to the activation and increase of various molecules, e.g.…”
Section: Introductionmentioning
confidence: 99%